«No es la religión de Cristo». La figura de Jesús de Nazaret en el socialismo español hasta 1936 - Joseba Louzao Villar (Amnis)
This article will explore the image of Jesus of Nazareth in Spanish socialism in the late nineteenth and early twentieth centuries, through its publications (El Socialista or La Lucha de Clases) and books. Until the thirties, socialism discussed this religious figure as an antecedent of socialism. For this reason, the image of Jesus became a central element of the anticlericals complaints within the normative conflict between catholicism and laicism.